Knowlege, Literacies and the teaching of reading English as a foreign language - Fernández Toledo, Piedad; Salager-Meyer, Françoise (International Journal of English Studies, 2009)
This paper addresses some key issues cutting across disciplinary fields and influencing EFL reading teaching and research. Reading models have been informed by Information and Knowledge Management paradigms, gradually focusing on different components of prior knowledge and schemata. Lexis has proven to be determinant in cognitive models, as it provides direct access to concepts, stocked as semantic propositions. But schemata are built in the speaker’s mind according to the individual experiences, depicting reading acts as meaning creation on a socio-pragmatic basis. Secondly, the parallel evolution of the Literacy and Reading concepts calls up for multi-literacy approaches, which integrate digital competence into the learning goals, as technologies force changes in information, the way we access it, and on the pedagogical approaches to learning, and to EFL reading. The role of overt teaching, meta-cognitive strategies and individual factors, such as motivation or attitudes, continue being the focus of present and future research.